(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2017)
Religion represents one of the benchmarks for the Romanian communities abroad. Each representative of our society becomes basically a symbol and a promoter of Romanism in the host country. Therefore, regardless of faith or belief, the contribution of each citizen or friend of Romania in promoting a real and honest image of our country abroad is very valuable.